The Effect of Women's Representations in the Board of Directors and Their Educational Background and the Concentration of Company Ownership on the Dividend Policy of Companies Listed on IDX - Monica Setyawan; Djuminah Djuminah (Budapest International Research and Critics University, 2022)
Phenomenon about presence woman in ranks directors companies in Indonesia start get attention until now. Existence gender diversity is also frequent linked with solution to problem from theory agency. Besides than gender diversity, concentration ownership and background behind board education can also affect existence policy payment dividends on a company. Destination main from study this is for give proof empirical about influence presence women on the board of directors in relation with policy distribution dividends. For give proof addition about influence concentration ownership company to policy distribution dividend in third sector companies listed on the Indonesia Stock Exchange. population used in the study this is three sector industry public (industry, real estate and necessities primary consumers) listed on the IDX in the period 2018 to 2019. Because of this data is secondary data, because that data collection carried out that is with method quoting, sorting and tabulating data direct from sources data acquisition above. From this process then use purposive sampling method. existence woman on the board of directors take effect to payment dividend to the holdersstock. Concentration ownership take effect positive to policy payment dividend no accepted. Ownership concentrated more choose for pay dividend more a little because they could maintain source power company in consideration, they than distribute it to holder stock. Background behind influential board education positive to policy dividends.